Дослідження методів планування складських процесів для оптимізації системи управління запасами комплектуючих для комп’ютерної техніки - Ткач, Є. В. (ХНУРЕ, 2023)
This article examines the study of best practices for effective planning of warehouse processes to optimize the system of inventory management of components for computer equipment. The relevance of the topic is emphasized, as well as the need to use advanced information and software technologies to meet the requirements of modern inventory management. To achieve this goal, the use of Anaconda is proposed as an ideal solution. In addition, the article emphasizes the advantages of using Python as a programming language, given its versatility and adaptability to different situations